Antidiabetic activity enhancement in streptozotocin + nicotinamide–induced diabetic rats through combinational polymeric nanoformulation - Rani R (International Journal of Nanomedicine, 2019)
Ruma Rani,1 Shakti Dahiya,1 Dinesh Dhingra,2 Neeraj Dilbaghi,1 Ajeet Kaushik,3 Ki-Hyun Kim,4 Sandeep Kumar11Department of Bio and Nano Technology, Guru Jambheshwar University of Science and Technology, Hisar 125001, India; 2Department of Pharmaceutical Science, Guru Jambheshwar University of Science and Technology, Hisar 125001, India; 3Center for Personalized Nanomedicine, Institute of NeuroImmune Pharmacology, Department of Immunology and Nano-Medicine, Herbert Wertheim College of Medicine, Florida International University (FIU), Miami, FL 33199, USA; 4Department of Civil and Environmental Engineering, Hanyang University, Seoul 04763, South KoreaBackground: The bioactive compounds glycyrrhizin (GL) and thymoquinone (TQ) have been reported for antidiabetic activity in pure and nanoformulation (NF) form. However, the antidiabetic effect of a combined nanoformulation of these two has not been reported in the literature. Here, a combinational nanomedicine approach was investigated to enhance the antidiabetic effects of the two bioactive compounds of GL and TQ (GT), in type 2 diabetic rats in reference to metformin.Methods: Two separately prepared NFs of GL (using polymeric nanoparticles) and TQ (using polymeric nanocapsules) were mixed to obtain a therapeutic cargo of nanomedicine and then characterized with respect to particle size, stability, morphology, chemical interaction, and in vivo behavior. Additionally, NFs were evaluated for their cytotoxic effect on Vero cell lines compared to the pure form. This nanomedicine was administered orally, both independently and in combination (pure form or NF) for 21 successive days to type 2 diabetic rats and the effect assessed in term of body weight, fasting blood-glucose level, and various biochemical parameters (such as lipid-profile parameters and HbA1c).Results: When these nanomedicines were applied in combined rather than individual forms, significant decreases in blood glucose and HbA1c and significant improvements in body weight and lipid profile were observed, despite them containing lower amounts than the pure forms. The treatment of diabetic rats with GL and TQ, when administered independently in either pure or NF forms, did not lead to favorable trends in any studied parameters.Conclusion: The administration of combined GT NFs exhibited significant improvement in studied parameters. Improvements in antidiabetic activity could have been due to a synergistic effect of combined NFs, leading to enhanced absorption of NFs and lesser cytotoxic effects compared to pure bioactive compounds. Therefore, GT NFs demonstrated potential as a new medicinal agent for the management of diabetes.Keywords: glycyrrhizin, thymoquinone, nanoformulation, antidiabetic, lipid profile, glycated hemoglobin